Students Responsibility Behavior Modification by Positive Reinforcement Contingency and Suggestion Technique - เย็นเอง, สราวุธ (Journal of Vocational Education in Agriculture, 2019)
The purpose of this study was to adjust the behavior of students in taking responsibility. The sampling method was purposive sampling of selected students who showed irresponsible behavior. There were 2 students from the total number of 6 students. There were 5 steps (1) Analyze the behavior of students before development, (2) Study concepts, principles and patterns of development, (3) Choose a development strategy, (4) Select equipment, create, and Inspect equipment quality, and (5) Adjust the behavior of students by using the development model that has already been defined. Behavior Modification Techniques was positive reinforcement contingency and suggestion technique. The statistics used for data analysis were percentage and mean. The results of the study were that learning activities using Behavior Modification Techniques of positive reinforcement contigency and suggestion techniques can improve the development of behavior of students in the direction of responsibility. The students received a development score of 46.50 percent, and received progressive score of 71.22 percent.